2020
DOI: 10.1002/ppul.24719
|View full text |Cite
|
Sign up to set email alerts
|

Ficolin‐1 gene (FCN1) −144 C/A polymorphism is associated with adverse outcome of severe pneumonia in the under‐five Egyptian children: A multicenter study

Abstract: Background Pneumonia is the foremost cause of child death worldwide. M‐ficolin is encoded by the FCN1 gene and represents a novel link between innate and adaptive immunity. Objectives To investigate the FCN1 −144 C/A (rs10117466) polymorphism as a potential marker for pneumonia severity and adverse outcome namely complications or mortality in the under‐five Egyptian children. Methods This was a prospective multicenter study that included 620 children hospitalized with World Health Organization‐defined severe p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…In addition, the rs7851696 variant in the FCN2 gene has been associated with delayed graft function and acute graft rejection in renal transplant patients (T allele = OR 1.71; 95% CI: 1.02-2.87, p value = 0.048) [ 22 ]; in other diseases such as vasculitis, ficolin-M expression is elevated in peripheral blood mononuclear cells and inflamed areas [ 23 ] and severe pneumonia in the Egyptian population [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the rs7851696 variant in the FCN2 gene has been associated with delayed graft function and acute graft rejection in renal transplant patients (T allele = OR 1.71; 95% CI: 1.02-2.87, p value = 0.048) [ 22 ]; in other diseases such as vasculitis, ficolin-M expression is elevated in peripheral blood mononuclear cells and inflamed areas [ 23 ] and severe pneumonia in the Egyptian population [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Variants of FCN1 gene and/or serum/plasma levels of ficolin‐1 were examined only in quite a few diseases (or pathological states) associated with autoimmunity such as rheumatoid arthritis [Vander Cruyssen et al., 2007], systemic lupus erythematosus [Addobbati et al., 2016], rheumatic fever and rheumatic heart disease [Catarino et al., 2018], type 1 diabetes mellitus [Anjosa et al., 2016], systemic inflammation [Munthe‐Fog et al., 2012], but also in some infectious diseases [Ren et al., 2014], such as leprosy [Boldt et al., 2013], pneumococcal disease [Kjaer et al., 2013], severe pneumonia [Elkoumi et al., 2020], as well as in sepsis [Świerzko et al., 2016]. It has been shown that plasma concentrations of ficolins may reflect the course of infection [Sokołowska et al., 2020; Świerzko et al., 2016; Świerzko et al., 2020].…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of another DMFT cut-off value, that is, DMFT =1, also revealed lack of significant differences in FCN1 genotype, allele, and haplotype frequencies between cases (children with DMFT ≥1) and controls (children free from caries, with DMFT =0) (results not shown). associated with autoimmunity such as rheumatoid arthritis [Vander Cruyssen et al, 2007], systemic lupus erythematosus [Addobbati et al, 2016], rheumatic fever and rheumatic heart disease [Catarino et al, 2018], type 1 diabetes mellitus [Anjosa et al, 2016], systemic inflammation [Munthe-Fog et al, 2012], but also in some infectious diseases [Ren et al, 2014], such as leprosy [Boldt et al, 2013], pneumococcal disease [Kjaer et al, 2013], severe pneumonia [Elkoumi et al, 2020], as well as in sepsis [Świerzko et al, 2016]. It has been…”
Section: The Distribution Of Genotypes and Frequency Of Alleles Of Fcn1mentioning
confidence: 99%
“…The myeloid cell compartment in the lungs of severe COVID-19 patients show an increased number of neutrophils, ficolin-1 (FCN1) þ monocytes, secreted phosphoprotein 1 (SPP1) þ monocyte-derived macrophages, and CD14 þ CD16 þ (Figure 2A and B) [26,29]. The FCN1 is a recognition molecule of the lectin complement pathway, and the high FCN1 level is associated with the severe inflammation during pneumonia [76,77]. Neutrophils infiltrated in the lungs of the severe COVID-19 patients are crucial innate immune cell generating broad type 1 IFN response, with a lesser extent to FCN1 þ monocytes ( Figure 2B) [29].…”
Section: Cellular Immune Response In Covid-19 Patientsmentioning
confidence: 99%